Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Metal–organic frameworks for modulating aging-associated redox–inflammatory microenvironments: Structural design, modes of action, and translational challenges - Hui Sun; Xian Dong; Yu Cao; Bingxu Huang; Dewei He; Daiyong Chao; Wenjin Guo; Shoupeng Fu (Chemical Engineering Journal, 2026)

Hydrological sensitivity and carbon dynamics during the evolution of a crater lake peatland in Northeast China - Yuefeng Li; Bo Ding; Zhengyu Xia; Yuwen Fu; Jingjing Sun; Zicheng Yu (CATENA, 2026)

Erratum to ‘Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media’ [Applied Clay Science 290 (2026) 108250] - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Decadal basin-wide nitrogen recovery and localized estuarine deterioration in the Bohai Sea revealed by physics-guided spatially adaptive machine learning - Ruiteng Sun; Yuan Li; Longwen Fu; Kun Wang; Jing Yu; Fengshuo Yang; Yanfang Li; Xiaoguang Li; Shichao Tian; Youcai Liu; Dejuan Jiang; Yongming Luo (Journal of Hydrology, 2026)

Interpretable and robust machine-learning prediction of CO2-H2O-coal wettability for deep CO2-enhanced coalbed methane and geological storage - Yunzhong Jia; Chenying Yu; Zhaolong Ge; Jiren Tang; Xiao Sun; Wenyu Fu (Gas Science and Engineering, 2026)

Single-mode topological state laser based on cholesteric liquid crystal microcapsules for ultra-high sensitivity detection of trace silver ions - Zhi Sun; Yu Zhao; Xiaowei Yang; Tao Chen; Yiqian Fu; Siyi Meng; Xiang Liu; Xiuhong Wang (Chemical Engineering Journal, 2026)

Decoupling of evapotranspiration from atmospheric demand: mechanistic insights into the local evaporation paradox in arid shrublands via physical and physiological resistance thresholds - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Shengjie Wang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Zhilan Wang; Meilin Sun; Peng Zhao; Shiquan Liu (Journal of Hydrology, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Quantifying the impact of vegetation changes on runoff in alpine basins using the Budyko framework integrating glacier effect - Zehui Zhou; Weidong Huang; Jiaxin Jin; Lei Yu; Wanqiu Xing; Jianyu Fu; Dianchen Sun; Bin Yong (Environmental Research, 2026)

Tracking Cretaceous to present day deep-sea sedimentary hiatuses driven by intensified bottom-water currents - Jiewei Hu; Dengfeng Li; David Chew; Simon W. Poulton; Yanhui Dong; Jinzhou Peng; Yu Fu; Xiaoming Sun (Earth and Planetary Science Letters, 2026)

Towards intensified oxidative coupling of methane in engineered non-uniform temperature fields - Xiaoyu Cui; Jincheng Huang; Yu Fu; Jun Zhang; Yuhan Sun (Chemical Engineering Journal, 2026)

Rapid and multimodal responsive composite hydrogel actuator with enhanced mechanical performance and reprogrammability for complex application scenarios in soft robotics - Zhilin Zhang; Xingchen Cui; Xing Gao; Xu Zhai; Zijing Huang; Jianwei Sun; Yi Tang; Yan Wang; Yu Fu; Tieqiang Wang (Chemical Engineering Journal, 2026)

Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Second-scale synthesis of oxygen-doped carbon nanotubes for oxygen reduction to hydrogen peroxide and valorization - Yining Sun; Jinze Li; Yu Fu; Zhenhua Li; Mingfei Shao (Science Bulletin, 2026)

In situ sulfides geochemistry and hydrothermal monazite UPb dating of the Jinchanggou gold deposit, Liaoning Province: Implication for the metallogenic age and ore-forming material sources - Songsong Wu; Peiwen Chen; Hao Zhang; Nantian Sun; Qingdong Zeng; Bing Yu; Guotao Sun; Yong Fu (Journal of Geochemical Exploration, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Organic matter controls rare earth element hyper-enrichment in Pacific deep-sea bioapatite - Xijiao Liao; Dengfeng Li; Simon W. Poulton; John R. Reinfelder; David Chew; Yu Fu; Yongjia Liang; Zhengkun Li; Jinzhou Peng; Xiaoming Sun (Geochimica et Cosmochimica Acta, 2026)

Bionic Tursiops Truncatus-inspired dual-mode sensor for proximity sensing and high-resolution tactile perception - Hang Yu; Zhao Xu; Haowen Chen; Guangchao Wang; Qiang Sun; Haoran Fu; Huaping Wu; Aiping Liu (Chemical Engineering Journal, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

DEM modelling of tillered wheat plants with dynamic parameter calibration for high-speed cutting simulation - Kai Sun; Jianqun Yu; Jun Fu; Yajun Yu; Jinwen Zhao; Long Zhou; Yang Wang (Biosystems Engineering, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Wearable and breathable double-sided alginate/silk fibroin aerogel-nanofiber-based flexible sensor for personal thermal management and distinguishable multimodal sensing applications - Yu Fu; Peng Liu; Zhenshuai Wan; Ye Tian; Peng Wang; Chong Liu; Peng Sun; Shaoshuai Li; Dengjie Zhu; Caixia Ren (Chemical Engineering Journal, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Reshaping inequalities in subjective well-being across multiple urban contexts: Evidence from over 2,000 communities in Beijing - Yu Zhu; Tianshun Gu; Qinyu Cui; Qiaoting Fu; Shijie Sun (Applied Geography, 2026)

Deep learning-driven detection of municipal sludge moisture content based on feature images of compressed slices - Guotao Wang; Yue Sun; Penghe Zhu; Shuaijun Yang; Zijun Du; Yuejia Chen; Fuchun Liu; Fu He; Xinlei Zhang; Tiefu Xu; Yu Tao (Journal of Environmental Management, 2026)

The role of biological uptake, coalification and hydrothermal overprinting on the formation of coal-hosted Ge deposits - Hao-Yu Sun; Mei-Fu Zhou (Journal of Asian Earth Sciences, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Holocene glaciers and climates inferred from quantitative reconstruction for the Rongbuk and Khumbu glaciers on the southern and northern slopes of the Mount Qomolangma - Ping Yu; Jiule Li; Xiangke Xu; Ping Fu; Hongjie Zhang; Yaqing Sun; Baiqing Xu (Journal of Geographical Sciences, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

The ATG14: multi-layer autophagy control and an emerging therapeutic target in cancer - Wenbo Wang; Chujuan Yu; Fulin Sun; Ruofeng Wang; Weikai Xia; Qinghang Song; Huhu Zhang; Zhenzhen Jia; Min Zhang; Haoran Wang; Zhenxiang Wang; Rong Fu; et al. (Apoptosis, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Biotic interactions driving the Centropages species co-existence in temporal Xiangshan Bay, China - Jieqing Yang; Yunrong Shi; Jinchen Yu; Lang Chen; Yuekai Wang; Tao Sun; Sen Li; Xinran Li; Qinghe Liu; Jing Fu; Wei Tian; Jin Zhou (Journal of Oceanology and Limnology, 2026)

Development of an inactivated H9N2 subtype avian influenza serological DIVA vaccine using the chimeric A/B NA epitope approach - Jingfeng Zhang; Zhiyu Fan; Qunxing Pan; Fei Yu; Huawei Sun; Minhua Sun; Jinping Fu; Jiasheng Song (Veterinary Microbiology, 2026)

The role of the nasal microbiome in linking ozone pollution to allergic rhinitis in children - Hao Tang; Shuang Du; Yongqiang Tan; Wen Su; Zhiping Niu; Jin Sun; WenPu Shao; Xinyi Fang; Zhiwei Tang; Dongjun Zhang; Zhuoru Chen; Zhenhua Zhang; et al. (Journal of Hazardous Materials, 2026)

UAV-based aboveground biomass estimation via trait-mediated pathways in a cultivated Leymus chinensis grassland - Lidong Cao; Yu Fu; Tianhang Zhao; Dekun Meng; Xiaoting Pan; Wei Sun (Journal of Environmental Management, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Organic molecule functionalization of Cu single-atom catalysts for enhanced electrocatalytic CO2 reduction to methane - Yihai Wu; Zhenchao Xu; Jianglan Chen; Hongyu Li; Yu Fu; Yuhan Sun; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Organophosphorus esters in edible seaweeds: Higher levels and different bioaccumulation patterns relative to terrestrial vegetables - Dongdong Fu; Wentao Lu; Chu Peng; Junjie Zhang; Yu Wang; Wei Zhou; Zhihua Feng; Hongwen Sun; Lei Wang (Food Chemistry, 2026)

In-situ constructed organic-copper bilayer SEI for exceptional cycling stability of Zn anodes - Jingwen Liu; Xinghui Liu; Teng Yu; Meiting Fu; Yibo Ma; Wenxiang Sun; Zhen Hong; Tianyi Ma; Lei Wang; Caixia Li (Chemical Engineering Journal, 2026)

A high-strength, heat-resistant, recyclable, and degradable ramie fiber-reinforced polyimine biocomposite - Pandeng Li; Tingting Liu; Gen Lu; Tong Shu; Tianyi Yu; Yuchen Zhao; Hengwei Fu; Junqi Yang; Haoping Du; Penghao Sun; Ziqi Hou; Chunhua Fu; et al. (Chemical Engineering Journal, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Contaminant migration in vadose zone beneath unregulated landfills with damaged geomembranes - Yu-Zhang Bi; Xin-Po Sun; Qi Zou; Zhe-Yuan Jiang; Xian-Lei Fu (Waste Management, 2026)

The CsWRKY3–CsHB7 transcriptional cascade promotes temperature-responsive peel pigmentation via CsCCD4b-mediated β-citraurin biosynthesis in citrus - Ranran Wei; Ang Fu; Yu Fang; Quan Sun; Zhijing Mo; Pengtao Yue; Ying Liang; Zongzhou Xie; Lijun Chai; Junli Ye; Xiuxin Deng (Molecular Plant, 2026)

On-demand thermal regulation and water harvesting via liquid metal-infused bio-inspired microchannel architectures - Chenfei Zhou; Yuanbo Sun; Yu Cheng; Chenyang Cai; Meng Zhang; Wang Zhang; Yu Fu (Journal of Cleaner Production, 2026)

Confinement-desolvation-interfacial matching trilogy boost wide-temperature-range zinc‑iodine batteries - Shang Sun; Hao Luo; Wenjing Zhang; Yu Fu; Fan Li; Min Zhou; Shunyao Li; Chi Chen; Hanna He; Lina Ma (Chemical Engineering Journal, 2026)

Corrigendum to “Chain confinement-induced photonic engineering in cellulose for SuFEx-click-chemistry-processed wearable thermal metamaterials” [523 (2025): 168683–154695/CEJ_168683] - Jing Liu; Xiaodan Wu; Bowen Jiang; Yuanbo Sun; Fulin Cheng; Yu Cheng; Chenyang Cai; Yu Fu (Chemical Engineering Journal, 2026)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Vapor-phase polymerization of polypyrrole in PVA hydrogels for enhanced electrical conductivity in multimodal sensing applications - Ruobing Tian; Yu Zhang; Yuanna Sun; Jiahao Liu; Xueming Tang; Jinlong Gao; Guixin Lv; Yan Jiang; Jun Fu (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Predicting and Optimizing Cotton Yield and Nitrogen-Phosphorus Fertilization Using the DSSAT Model and Ecological Stoichiometry Theory - Zhuo Yu; Meiwei Lin; Yi Chen; Xiaoju He; Kai Lu; Kairui Wen; Weihong Sun; Weiguo Fu (Journal of Soil Science and Plant Nutrition, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Impact of Built Environment on Urban Vitality in Shrinking Cities: Moderating Effect of Housing Vacancy - Hui Fu; Guolei Zhou; Hongri Sun; Yu Jin; Hanchun Wu; Yanjun Liu (Chinese Geographical Science, 2025)

Cover Image - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)

Detection and Genomic Characterisation of Scale Drop Disease Virus (SDDV) in Farmed Yellowfin Seabream ( Acanthopagrus latus ) in Southern China - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Scale drop disease virus (SDDV) is a distinct member of the genus Megalocytivirus within the family Iridoviridae , which was recently identified as a causative agent of yellowfin seabream Acanthopagrus latus ascitic diseases (YFSBAD). Here, a molecular surveillance of SDDV in pond‐cultured yellowfin seabream was conducted during 2021 to 2023 in Zhuhai, the most significant breeding region for this fish species in China. A total of 73 batches of naturally diseased yellowfin seabream samples were collected for SDDV detection. As a result, 31 samples were confirmed SDDV positive by conventional PCR detection, among which 9 additional SDDVs were isolated by using MFF‐1 cell line, and 4 isolates were further validated by monoclonal antibody‐based immunofluorescence assays. Multiple alignment and phylogenetic analysis revealed that these isolates shared the identical mcp sequences and were clustered within the same clade. Additionally, the complete genome sequence of a new SDDV isolate (SDDV‐ZH918/23) was determined and annotated. The result shows that SDDV‐ZH918/23 consists of 131,741 bp and encodes 143 putative open reading frames. The genome collinearity analysis demonstrated very high nucleotide similarity among all SDDV isolates distributed in China and other Asian countries. Unexpectedly, a 152 bp deletion mutant was also found in two SDDV isolates. Collectively, our study once again demonstrates that SDDV acts as an emerging etiological agent in farmed yellowfin seabream, and a partial deletion mutant of the SDDV genome was first recorded.

Glycemic status-dependent proteomic signatures of biological aging for health risk prediction - Jiang Li; Jie Li; Xiaoqin Xu; Yuefeng Yu; Wenqi Shen; Ying Sun; Yanqi Fu; Xiao Tan; Ningjian Wang; Yingli Lu; Bin Wang (GeroScience, 2025)

Full waveform inversion of cross-hole GPR data using Markov Chain Monte Carlo method based on SE-Resnet - Sheng-chao Wang; Yu-fei Wang; Yi-fei Liu; De-fu Zhang; Hui Sun; Gong-min Chen; Xiang-yu Tan (Applied Geophysics, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Enhanced piezo-Fenton synergies enabled by interface-engineered 0D/3D heterojunctions (Fe2O3 QDs@BTO): investigation of interfacial behavior and reaction mechanism - Shuai Liu; Xueyao Wang; Xuyang Hu; Lihui Huang; Ting Sun; Lingshuai Kong; Zhenhui Gao; Rongbing Fu; Yu Xiao (Chemical Engineering Journal, 2025)

Chain confinement-induced photonic engineering in cellulose for SuFEx-click-chemistry-processed wearable thermal metamaterials - Jing Liu; Xiaodan Wu; Bowen Jiang; Yuanbo Sun; Fulin Cheng; Yu Cheng; Chenyang Cai; Yu Fu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Potential for hydroxamic acid modification via electronic effect: A case study of enhanced cassiterite flotation - Zhifeng Zhang; Yao Yu; Junhao Fu; Jian Cao; Chaozheng Deng; Wei Sun; Haisheng Han (Minerals Engineering, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Enhanced comprehensive recovery of wolframite via novel aromatic heterocyclic hydroxamic acid in metal-based complex system - Zhifeng Zhang; Junhao Fu; Yao Yu; Haisheng Han; Wei Sun (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

The isolation and immunoprotective efficacy of outer membrane vesicles of Dichelobacter nodosus - Xianjing He; Yu Shi; Jiao Liu; Shan Fu; Baiqi Wang; Bao Li; Yujia Sang; Kai Jiang; Dongbo Sun; Donghua Guo (Veterinary Microbiology, 2025)

Faster soil organic carbon turnover in MAOM versus POM: straw input causes larger microbial driven soil organic carbon decomposition but higher straw accumulation in MAOM - Xiongsheng Yu; Lili Wang; Qiang Wang; Guoyan Zhou; Han Sun; Georg Guggenberger; Yongfu Li; Kuzyakov Yakov; Yu Luo; Yingyi Fu (Soil and Tillage Research, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Efficient recovery of Th and rare earth from radioactive residue leachate using synthesized amide carboxylic acids: Mechanistic study and process development - Xinyu Fu; Yun Gao; Peilin Lei; Hepeng Zhang; Guisu Yu; Zhong Tian; Xiaoqi Sun (Journal of Environmental Management, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Ethanolic extract of Duea ching (Ficus botryocarpa Miq.) fruit: Antioxidant activity and enhancement of physical property and oxidative stability of Asian seabass oil-in water emulsion - Varsha Likhar; Natchaphol Buamard; Umesh Patil; Xiaohui Sun; Fu Yu; Bin Zhang; Soottawat Benjakul (Food Chemistry, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Injectable short-fiber hydrogel with fatigue resistance and antibacterial properties for synergistic periodontitis therapy - Zhihui Han; Luhan Bao; Yuedi Yu; Yue Zhao; Manying Wang; Yang Sun; Minna Fu; Qianrong Zhou; Wenjuan Liu; Wenguo Cui; Youcheng Yu (Chemical Engineering Journal, 2025)

MaC14a: An AI-enhanced CRISPR-Cas14a microfluidic platform for accurate on-site detection of geminiviruses in tomato plants and whiteflies - Zhengziang Huang; Guofang Ma; Ruibin Hu; Jian Xu; Yali Fu; Jintian Tang; Dong Li; Zhijuan Chen; Xuping Shentu; Zihong Ye; Kai Sun; Xiaoping Yu (Chemical Engineering Journal, 2025)

Donor macrophage pyroptosis contributes to the development of aGVHD - Xueyan Sun; Qingyuan Qu; Qi Chen; Fengqi Liu; Haixia Fu; Yuxiu Chen; Menglin Li; Yun He; Xiaolu Zhu; Xiangyu Zhao; Yu Wang; Xiaojun Huang; et al. (Science China Life Sciences, 2025)

miR-7002-5p targets caspase-1 to suppress the inflammatory response of macrophages induced by Streptococcus equi subsp. zooepidemicus - Honglin Xie; Jingfei Deng; Jingyu Yu; Shun Li; Yibo Wang; Yajuan Li; Yunfei Huang; Qinqin Sun; Jiedan Liao; Ziteng Deng; Qiang Fu (Archives of Microbiology, 2025)

Efficient moisture energy harvesting through electronegativity enhancement and dual-gradient asymmetric structural design - Mingxing Jing; Yiyang Fu; Yu Yang; Hongyuan Zhu; Wensheng Wang; Han Wu; Zhuangzhi Sun (Journal of Environmental Chemical Engineering, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Screening of monascus SPP. and regulation effects of quorum sensing molecules and co-factors based on tocopherol high-accumulation - Jingyi Fu; Qifeng Wu; Liu Tang; Yixiang Zhang; Shiji Sun; Yu Zheng; Anyan Wu; Likang Qin; Haiying Zeng (Food Bioscience, 2025)

Atomic-level defect engineering enables hollow ternary molybdenum phosphoselenide nanospheres for enhanced sodium-ion storage - Yao Guo; Yangjie Liu; Lihong Xu; Mujtaba Aminu Muhammad; Huiling Fang; Jiaqi Yu; Mengyao Tu; Xiang Hu; Chuan-Fu Sun; Zhenhai Wen (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The effects of 17β-trenbolone and bisphenol A on sexual behavior and social dominance via the hypothalamic-pituitary-gonadal axis in male mice - Xiang Zuo; Minghe Sun; Huijuan Bai; Shuhui Zhang; Jialu Luan; Qian Yu; Zhenhua Fu; Qili Zhao; Mingzhu Sun; Xin Zhao; Xizeng Feng (Journal of Environmental Sciences, 2025)

Unveiling potential of capacitive deionization: Memory-electrostatic synergy for enhanced ion removal and electrode regeneration - Fulin Cheng; Jing Liu; Yuxin Ji; Yuanbo Sun; Jilong Duan; Chenyang Cai; Yu Fu (Desalination, 2025)

Ambient-temperature α-pinene hydrogenation to cis-pinane over Ru/CeO2-H catalyst via the dimethyl-up configuration - Yu-Xuan Fu; Shu-Yi Huang; Ming-Shuai Sun; Yan Zhou; Dan-Dan Cai; Wen-Shuai Zhu; Wei Hui; Duan-Jian Tao (Chemical Engineering Journal, 2025)

Evaluation and identification of reference genes for qRT-PCR analysis in bermudagrass roots under alkaline salt stress - Lisi Tang; Qikun Yu; Wen Li; Zongjiu Sun; Chao Fu; Guozhi Hu; Zhengfa Yu; Shirui Ma; Peiying Li (Physiology and Molecular Biology of Plants, 2025)

Assessment of the electrocoagulation coupled with E-peroxone for ultrafiltration fouling mitigation for shale gas produced water treatment - Shi-gang Chen; Guang-dong Sun; Fan-xin Kong; Yu-Xuan Chen; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe/Mg-modified lignocellulosic biochar on in vitro ruminal microorganism fermentation of corn stover - Yuping Liu; Jiyu Sun; Taotao Zhao; Lin Wang; Chenyu Zhao; Jingjing Fu; Dawei Li; Haiye Yu (Bioresource Technology, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhanced heat retention and energy efficiency in photothermal membranes via sealed light-absorbing cavity engineering - Yibo Wang; Yuanbo Sun; Fulin Cheng; Zechang Wei; Chenyang Cai; Yu Fu (Chemical Engineering Journal, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Toxic effects of exposure to polymethyl methacrylate and polyvinyl chloride microplastics in Pacific oysters (Crassostrea gigas) - Chunmei Gao; Zhuolong Wu; Baogui Liang; Jikun Lu; Guanghui Fu; Miaomiao Sun; Wenwen Yu; Shuo Zhang; Shike Gao (Environmental Pollution, 2025)

MRG15 promotes cell apoptosis through inhibition of mitophagy in hyperlipidemic acute pancreatitis - Boyuan Gu; Wenhao Yu; Zhiwei Huang; Junjie Bai; Shenglu Liu; Bingyu Ren; Pengru Wang; Lei Sun; Jian Wen; Yang Zheng; Peng Tan; Wenguang Fu (Apoptosis, 2025)

Structural characteristics of areca nut seed neutral polysaccharide and its impact on gut microbiota from human feces - Mengfan Zhang; Haining Zhuang; Xiaowei Zhang; Xiaoyu Wang; Xia Fu; Sheng Chen; Lingyun Yao; Huatian Wang; Min Sun; Chuang Yu; Heng Yue; Tao Feng (Food Hydrocolloids, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Lignosulfonate modified zero-valent iron enhanced activation of peroxymonosulfate for sulfamethazine removal: Performance and mechanism - Yao Duan; Xiaoyu Li; Shang Gao; Minyi Yu; Lichun Fu; Ying Zhang; Haiyang Sun; Yuwei Pan (Chemical Engineering Journal, 2025)

Transition metal doped MoS2 for piezoelectric Fenton-catalyzed degradation of norfloxacin: Rapid innergenerated-H2O2 conversion and dual pathways of non-radicals and radicals - Xueyao Wang; Shuai Liu; Lihui Huang; Ting Sun; Lingshuai Kong; Zhenhui Gao; Rongbing Fu; Yu Xiao (Chemical Engineering Journal, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Magnesium isotope constraints on the role of recycled carbonate-rich sediments in the formation of ultrapotassic magmatic rocks at a continental arc setting - Yu Chen; Yi-Xiang Chen; Fatma Gülmez; Ş. Can Genç; Guo-Chao Sun; Zi-Fu Zhao (Lithos, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

Synthesis of CoFe2O4@C based on Fe/Co-BTC for efficient detection, determination and degradation of nitenpyram residue: An electrochemical study, condition optimization and mechanism - Yuan-Zhen Wang; Guo-Qiang Xu; Yu-Han Sun; Liu Yang; Yu-Long Liu; Ying Fu (Journal of Cleaner Production, 2024)

Assessment of groundwater quality variation characteristics and influencing factors in an intensified agricultural area: An integrated hydrochemical and machine learning approach - Zexin Wu; Yao Wu; Yexiang Yu; Lei Wang; Peng Qi; Yingna Sun; Qiannian Fu; Guangxin Zhang (Journal of Environmental Management, 2024)

Three-dimensional porous Ti supported Ni/Sb Co-doped SnO2 anode for electrocatalytic production of ozone - Mengqing Hu; Di Zhao; Mengyang Dong; Huai Qin Fu; Yu Zou; Yiming Xu; Ming Zhou; Lei Zhang; Liang Wang; Yajie Shu; Kaidi Zhang; Ziyao Chen; et al. (Journal of Environmental Chemical Engineering, 2024)

Changes in the key odorants of loose-leaf dark tea fermented by Eurotium cristatum during aging for one year: Focus on the stale aroma - Shanshan Shen; Jialin Fu; Ranqin Fan; Jixin Zhang; Haoran Sun; Yu Wang; Jingming Ning; Pengxiang Yue; Liang Zhang; Xueling Gao (Food Research International, 2024)

Utilizing superheated steam to prepare traditional Chinese twice-cooked pork bellies, exploring its effects on the texture and flavor of fat layers - Mi Tang; Xin Feng; Liang Ma; Yong Yu; Hankun Zhu; Yu Fu; Kangting Sun; Xiaoqian Wu; Jinyong Wang; Xiang Li; Yuhao Zhang (Meat Science, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

The dietary supplementation of Sargassum fusiforme can effectively alleviate high-fat diet induced metabolic abnormalities - Yu Bai; Yuanyuan Fu; Kang Chen; Yan Sun; Chengxu Zhou; Jichang Han; Xiaojun Yan (Algal Research, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Controls on the facies and architecture evolution of a fan delta in Qinghai Lake, China - Di Ma; Xinghe Yu; Shunli Li; Zhijie Zhang; Chao Fu; Hongwei Sun; Chun Liu (Frontiers of Earth Science, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Regrowth or smart decline? A policy response to shrinking cities based on a resilience perspective - Yu Jin; Guolei Zhou; Hongri Sun; Hui Fu; Hanchun Wu; Yanjun Liu (Sustainable Cities and Society, 2024)

Dynamics changes in metabolites and pancreatic lipase inhibitory ability of instant dark tea during liquid-state fermentation by Aspergillus niger - Haoran Sun; Ranqin Fan; Rui Fang; Shanshan Shen; Yu Wang; Jialin Fu; Rui Hou; Runchen Sun; Shinuo Bao; Qi Chen; Pengxiang Yue; Xueling Gao (Food Chemistry, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Two new diarylheptanoids from the green walnut husks of Juglans mandshurica Maxim. - Yuan-Yuan Zhou; Ning-Yu Liu; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Qi-Feng Fu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Does fintech positively moderate the impact of mineral resources on green growth? Role of economic policy uncertainty in OECD economies - Fu Chen; Weiwei Zhang; Fangfang Li; Yongtai Sun; Huiyuan Yu (Resources Policy, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

An eco-friendly and high-yield extraction of rare earth from the leaching solution of ion adsorbed minerals - Guisu Yu; Hepeng Zhang; Zhong Tian; Yun Gao; Xinyu Fu; Xiaoqi Sun (Journal of Hazardous Materials, 2024)

Effects of saturated fluids on petrophysical properties of hot dry rock at high temperatures: An experimental study - Qiuyan Wang; Daobing Wang; Wei Fu; Chen Zheng; Dongliang Sun; Bo Yu (Geothermics, 2024)

Combined multi-omics approach to analyze the flavor characteristics and formation mechanism of gabaron green tea - Dongzhu Huang; Dongqiao Zheng; Chenyi Sun; Maoyin Fu; Yuhan Wu; Hong Wang; Jieyao Yu; Yunqiu Yang; Yeyun Li; Xiaochun Wan; Qi Chen (Food Chemistry, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

Dust exposure linkages among Asian countries - Chaowei Zhou; Xiaoming Feng; Ruibo Zhao; Yichu Huang; Yu Zhang; Xuejing Leng; Chuanlian Sun; Yihe Lü; Bojie Fu (Journal of Cleaner Production, 2024)

The investigation of oxygen species in silicalite-1 supported MnOx-Na2WO4 catalyst towards efficient oxidative coupling of methane - Yujie Wang; Wenbo Kong; Yu Fu; Lei Zheng; Bingrong Pan; He Zhu; Shuqing Li; Jiong Li; Jun Zhang; Yuhan Sun (Journal of Environmental Chemical Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Immunosuppressive steroids quadrilisteroids A−C and derivatives from the terrestrial fungus Aspergillus quadrilineatus - Yu Chen; Qin Li; Yu Liang; Mengsha Wei; Hong Liao; Aimin Fu; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

NUFIP1-engineered exosomes derived from hUMSCs regulate apoptosis and neurological injury induced by propofol in newborn rats - Wen Sun; Pengyue Zhao; Shidong Hu; Zhenting Zhao; Boyan Liu; Xingpeng Yang; Jiaqi Yang; Ze Fu; Songyan Li; Wenli Yu (NeuroToxicology, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Pyrolysis characteristics and evolution of the organics in Nong’an oil shale lump during sub-critical water extraction - Jingjing Gu; SunhuaDeng; Huafei Fu; Dongxue Yu; Weidong Tang; Youhong Sun; Wei Guo; Weiguang Shi (Fuel, 2024)

Efficient detection of flusilazole by an electrochemical sensor derived from MOF MIL-53(Fe) for food safety - Yu-Han Sun; Liu Yang; Xian-Xian Ji; Yuan-Zhen Wang; Yu-Long Liu; Ying Fu; Fei Ye (Food Chemistry, 2024)

Phototherapy-based multifunctional nanoplatform for synergistic therapy against drug resistance bacteria: Progress, advances and challenges - Bingqian Yu; Qirui Liu; Jiadi Sun; Xuran Fu; Yinzhi Zhang; Xiulan Sun (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Improving prediction of N2O emissions during composting using model-agnostic meta-learning - Shuai Shi; Jiaxin Bao; Zhiheng Guo; Yue Han; Yonghui Xu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Nana Jiang; Lei Sun; Xinda Liu; Wanying Liu; Nuo Chang; et al. (Science of The Total Environment, 2024)

Interactive scheduling optimization of regional multi-agent integrated energy systems considering uncertainties based on game theory - Yu Fu; Qie Sun; Ronald Wennersten; Xueyue Pang; Weixiong Liu (Journal of Cleaner Production, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Unraveling biological behavior and influence of magnetic iron-based nanoparticles in algal-bacterial systems: A comprehensive review - Zhijun Ren; Ruiyao Fu; Li Sun; Huixue Li; Zijia Bai; Yu Tian; Guangming Zhang (Science of The Total Environment, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Combustion and emission characteristics of CNG/gasoline DFSI engine with CNG direct injection - Ping Sun; Huamei Zhu; Song Yang; Wei Dong; Xiumin Yu; Zhihao Fu (Fuel, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

The impacts of nitrogen addition on the active carbon pools in forest soils along an urban–rural gradient - Ruoxian Fu; Yuanchun Yu; Yue He; Xiaoniu Xu; Xu Sun; Jun Yang; Xiao Tao (CATENA, 2024)

Effects of phosphate on REY adsorption by goethite: Insights into REY enrichment and release in marine iron oxyhydroxides during early diagenesis - Yongjia Liang; Xiaoming Sun; Dengfeng Li; Caroline L. Peacock; Yu Fu (Chemical Geology, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

Genomic evidence for climate-linked diversity loss and increased vulnerability of wild barley spanning 28 years of climate warming - Yu Zhou; Ruilian Song; Eviator Nevo; Xiaoqin Fu; Xiaofang Wang; Yixiang Wang; Chengyang Wang; Junpeng Chen; Genlou Sun; Dongfa Sun; Xifeng Ren (Science of The Total Environment, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Imbalance in lake variability but not embodying driving factors on the Qinghai-Tibetan Plateau calls on heterogeneous lake management - Xuejing Leng; Xiaoming Feng; Yu Feng; Chuanlian Sun; Xiaochi Liu; Yu Zhang; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Environmental Management, 2024)

Investigating enzyme kinetics and fluorescence sensing strategy of CRISPR/Cas12a for foodborne pathogenic bacteria - XuRan Fu; JiaDi Sun; Bingqian Yu; Yongli Ye; Lina Sheng; Jian Ji; Jiayu Zheng; Minghong Fan; Jingdong Shao; XiuLan Sun (Analytica Chimica Acta, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Inhibiting release of phenanthrene from rice-crab coculture sediments to overlying water with rice stalk biochar: Performance and mechanisms - Nan Sun; Tianyi Wang; Bowei Qi; Shijie Yu; Zhongbao Yao; Guanglei Zhu; Qiang Fu; Chenyang Li (Science of The Total Environment, 2024)

Ultrasonic vibration enabled under-liquid forming of metallic glasses - Xin Li; Luyao Li; Sajad Sohrabi; Jia’nan Fu; Zhen Li; Zhe Chen; Rongce Sun; Yu Zhang; Jinbiao Huang; Heting Zhang; Jian Zhu; Xiangyan Chen; et al. (Science Bulletin, 2024)

Exploiting bifunctional 3D-Printed geopolymers for efficient cesium removal and immobilization: An approach for hazardous waste management - Siqi Ma; Shuai Fu; Hualong Yang; Peigang He; Zhenlin Sun; Xiaoming Duan; Dechang Jia; Paolo Colombo; Yu Zhou (Journal of Cleaner Production, 2024)

Housing vacancy identification in shrinking cities based on multi-source data: A case study of Fushun city in Northeast China - Hongri Sun; Guolei Zhou; Yanjun Liu; Hui Fu; Yu Jin (Journal of Geographical Sciences, 2024)

Cultivation and biogeochemical analyses reveal insights into biomineralization caused by piezotolerant iron-reducing bacteria from petroleum reservoirs and their application in MEOR - Hao Dong; Li Yu; Ting Xu; Yulong Liu; Jian Fu; Yanlong He; Ji Gao; Jiaqi Wang; Shanshan Sun; Yuehui She; Fan Zhang (Science of The Total Environment, 2023)

Evolution of social-ecological system and the hydrological linkages in oasis area, northwestern China - Yu Zhang; Xiaoming Feng; Chuanlian Sun; Xuejing Leng; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Arid Environments, 2023)

Integration of Sentinel–1 and Landsat–8 data for identifying deformation risk of hydraulic engineering in seasonally frozen salinization regions - Zhaoxi Wang; Chen Cao; Qingbo Yu; Xin Xu; Qing Wang; Cencen Niu; Jiejie Shen; Mengxia Han; Huicheng Fu; Kuanxing Zhu; Jing Liu; Weitong Xia; et al. (CATENA, 2023)

Toward a sound understanding of a large-scale landslide at a mine waste dump, Anshan, China - Shu-wei Sun; Liu Liu; Zhao-xi Yang; Xin-yu Fu (Landslides, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Modeling potential arsenic enrichment and distribution using stacking ensemble learning in the lower Yellow River Plain, China - Wengeng Cao; Yu Fu; Yanpei Cheng; Wenhua Zhai; Xiaoyue Sun; Yu Ren; Deng Pan (Journal of Hydrology, 2023)

Light-driven sustainable enhancement of Cr(VI) reduction via the combination of Cr(VI)-reducing bacteria, Paraclostridium bifermentans with CdS nanoparticles - Yilin Le; Xing He; Mengnan Liu; Xue Liu; Shidong Zhou; Rongrong Xie; Yu Fu; Huilei Wang; Jianzhong Sun (Journal of Environmental Chemical Engineering, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Impact of environmental characteristics on children's gut microbiota – A pilot study in assessing the role of indoor microbiome and metabolites - Mei Zhang; Hao Tang; Yang Chen; Zhuoru Chen; Yanyi Xu; Xi Fu; Yu Sun; Zhuohui Zhao (Environmental Research, 2023)

A simple, natural 3D honeycomb structure achieving high photothermal conversion and sustainable salt-resistance for efficient desalination and potential electricity generation - Mingxing Jing; Wensheng Wang; Yiyang Fu; Yu Yang; Wenlong Song; Zhuangzhi Sun (Desalination, 2023)

Additive manufacturing of hierarchical Zeolite-A lattices with exceptionally high Cs+ adsorption capacity and near-unity immobilization efficiency - Siqi Ma; Hualong Yang; Shuai Fu; Yi Hu; Peigang He; Zhenlin Sun; Xiaoming Duan; Dechang Jia; Paolo Colombo; Yu Zhou (Chemical Engineering Journal, 2023)

Solution plasma-assisted synthesis of oxyhydroxides for advanced electrocatalytic water splitting - Wentao Bao; Ke Lu; Pengjie Fu; Jinfeng Yang; Ying Tang; Yaxin Sun; Zhen Yang; Fuxi Bao; Zongyuan Wang; Xiaodong Yang; Feng Yu (Chemical Engineering Journal, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Regulation mechanism of ionic strength on the ultra-high freeze-thaw stability of myofibrillar protein microgel emulsions - Mi Tang; Yi Sun; Xin Feng; Liang Ma; Hongjie Dai; Yu Fu; Yuhao Zhang (Food Chemistry, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Correlation of heavy metals’ exposure with the prevalence of coronary heart disease among US adults: findings of the US NHANES from 2003 to 2018 - Xi Li; Dongdong Zhang; Yang Zhao; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Environmental Geochemistry and Health, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

Upregulation of mitochondrial calcium uniporter contributes to paraquat-induced neuropathology linked to Parkinson’s disease via imbalanced OPA1 processing - Weixia Duan; Cong Liu; Jie Zhou; Qin Yu; Yu Duan; Tian Zhang; Yuanyuan Li; Guanyan Fu; Yapei Sun; Jiacheng Tian; Zhiqin Xia; Yingli Yang; et al. (Journal of Hazardous Materials, 2023)

Tuning strong metal-support interactions to boost activity and stability of aluminium nitride supported nickel catalysts for dry reforming of methane - Shuqing Li; Yu Fu; Wenbo Kong; Jiyang Wang; Changkun Yuan; Bingrong Pan; He Zhu; Xia Chen; Yidan Zhang; Jun Zhang; Yuhan Sun (Fuel, 2023)

Off-design characteristics of energy conversion equipment in integrated energy systems - Yu Fu; Haiyang Lin; Biao Feng; Cuiping Ma; Qie Sun; Ronald Wennersten (Journal of Cleaner Production, 2023)

Sulfur-containing adsorbent made by inverse vulcanization of sulfur/oleylamine/potato starch for efficient removal of Hg(II) ions - Yu Sun; Chengyue Yang; Yong Fu; Tuanyu Guo; Guiyang Yan; Jianshe Hu (Journal of Environmental Chemical Engineering, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

A 209,000-year-old history of methane seepage activity controlled by multiple factors in the South China Sea - Ganglan Zhang; Jun Cao; Yinan Deng; Hongfei Lai; Xuexiao Jiang; Yunxin Fang; Zenggui Kuang; Shengxiong Yang; Qianyong Liang; Piaoer Fu; Tiantian Sun; Meng Jin; et al. (Marine and Petroleum Geology, 2023)

Diagnosing the compound seasonal soil moisture-hydroclimate interaction regime on the Tibetan Plateau using multi-high-resolution reanalysis products and one regional climate model - Di Liu; Zhongbo Yu; Haishen Lü; Huanghe Gu; Chuanguo Yang; Qin Ju; Jiaqian Sun; Xiaolei Fu (Journal of Hydrology, 2023)

Myofibrillar protein microgels stabilized high internal phase Pickering emulsions with heat-promoted stability - Hongjie Dai; Yi Sun; Xin Feng; Liang Ma; Hai Chen; Yu Fu; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

An enhanced tilted-angle acoustic tweezer for mechanical phenotyping of cancer cells - Hanlin Wang; Joe Boardman; Xiaoyan Zhang; Chao Sun; Meng Cai; Jun Wei; Zhiqiang Dong; Mingqian Feng; Dongfang Liang; Sheng Hu; Yu Qian; Shuang Dong; et al. (Analytica Chimica Acta, 2023)

Characterization of dissolved organic matter in biochar derived from various macroalgae (Phaeophyta, Rhodophyta, and Chlorophyta): Effects of pyrolysis temperature and extraction solution pH - Yangzhi Liu; Shanshan Zhou; Yu Fu; Xiumei Sun; Tiejun Li; Chenghu Yang (Science of The Total Environment, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

Modeling of Mixed Cracks in Rock-Like Brittle Materials Under Compressive Stresses by a Double-Phase-Field Method - Zhan Yu; Yue Sun; Minh-Ngoc Vu; Jian-Fu Shao (Rock Mechanics and Rock Engineering, 2023)

The potential meat flavoring generated from Maillard reaction products of wheat gluten protein hydrolysates-xylose: Impacts of different thermal treatment temperatures on flavor - Ao Sun; Lining Chen; Wei Wu; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Food Research International, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Biochar-assisted anaerobic membrane bioreactor towards high-efficient energy recovery from swine wastewater: Performances and the potential mechanisms - Gaojun Wang; Guohao Liu; Gaofei Yao; Peng Fu; Changxi Sun; Yu Li; Qian Li; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Development of an interpretable machine learning model associated with heavy metals’ exposure to identify coronary heart disease among US adults via SHAP: Findings of the US NHANES from 2003 to 2018 - Xi Li; Yang Zhao; Dongdong Zhang; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Chemosphere, 2023)

Insights into the role of the microbial community lifestyle strategies in variations of the dissolved organic matter molecular composition along an effluent-dominated river - Xing Wang; Minda Yu; Xiaosong He; Jing Su; Beidou Xi; Yuanyuan Sun; Xuemei Fu; Yaojia Wang; Mingxia Zheng (Chemosphere, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Integrated multi-omic analyses on yellow Flammulina filiformis cultivar reveal postharvest oxidative damage responses - Yu Fu; Hao Tan; Bo Wang; Weihong Peng; Qun Sun; Yang Yu (Postharvest Biology and Technology, 2023)

Genesis and prospecting significance of the Buziwannan gold-polymetallic ore deposit in the West Kunlun Orogen Belt, China: Constraints from mineral geochemistry and in situ S–Pb isotope analyses of sulfides - Peiwen Chen; Qingdong Zeng; Lingli Zhou; Bing Liu; Yong Fu; Guotao Sun; Bing Yu; Zhen Long (Journal of Geochemical Exploration, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Design and Optimization of Multipoint Sampler for Seafloor Sediment Carried by a Deep-Sea Landing Vehicle - Yan Gao; Yue Zhou; Wei Guo; Yifan Fu; Sen Gao; Zhenzhuo Wei; Hongming Sun; Yu Sun (Journal of Marine Science and Engineering, 2022)
The present study proposes a low-energy consumption multipoint sampler carried by a deep-sea landing vehicle (DSLV) to meet the requirements of time series sampling in local areas and location series sampling in wide areas, and an optimization method of sampling structure based on least-squares support-vector machine (LSSVM) surrogate model and a multi-objective particle swarm optimization (MOPSO) algorithm. First, the overall structure and core components, such as the multipoint sampler’s sampling structure, were designed. The optimization variables were the cone angle, sampling tube inner diameter, and sampling tube inner hole length, which were determined by considering the force with which the sampling structure penetrates the seafloor sediment. Then, the sampling process was simulated by the finite element method-smoothed particle hydrodynamics (FEM-SPH) method, while the accurate LSSVM model of force required for sampling and sampling tube volume was established. Finally, the MOPSO algorithm was used for multi-objective optimization of model parameters of sampling structure. The optimal model of sampling structure that can provide theoretical support for the optimal design of multipoint sampler effectively reduces energy consumption and improves sampling efficiency by force required for sampling 25.89% lower and sampling tube volume 34.81% higher than the original model.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Moderate exercise relieves fluoride-induced liver and kidney inflammatory responses through the IKKβ/NFκB pathway - Yanghuan Yu; Ruiyan Niu; Fangye Zhao; Yangfei Zhao; Jinglu Wang; Jixiang Wang; Qiqi Cao; Rong Fu; Mohammad Hassan Nateghahmadi; Zilong Sun (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Study on the seasonal variations of dimethyl sulfide, its precursors and their impact factors in the Bohai Sea and North Yellow Sea - Yu Guo; Liying Peng; Zishi Liu; Xiaoting Fu; Guicheng Zhang; Ting Gu; Danyang Li; Jun Sun (Frontiers in Marine Science, 2022)
Dimethyl sulfide (DMS) is one of the most important volatile biogenic sulfur compounds and plays a significant role in global climate change. Studying the seasonal variations and the environmental factors that affect the concentration of DMS would aid in understanding the biogeochemical cycle of sulfur compounds. Using benzene-assisted photoionization positive ion mobility spectrometry (BAPI-PIMS), the seasonal distribution and the key impact factors of DMS and dimethylsulfoniopropionate (DMSP) in the Bohai Sea and North Yellow Sea were investigated in the summer and autumn of 2019. The concentrations of DMS and its precursors, DMSPp and DMSPd, in the surface seawater were 0.11–23.90, 0.67–41.38, and 0.03–12.28 nmol/L, respectively, in summer, and 0.10–20.79, 0.39–13.51, and 0.18–20.58 nmol/L, respectively, in autumn. The air-to-sea exchange flux of DMS was 43.05 ± 44.52 and 34.06 ± 63.38 μmol/(m·d), respectively, in summer and autumn. The results demonstrated that the temperature was the most dominant environmental factor, and the abundance of dinoflagellates was the most dominant biological factor that affected the distribution of DMS and DMSP in summer. The abundance of diatoms was the most dominant biological factor, and the levels of PO 4 3- , NO 2 - , NO 3 - , and SiO 3 2- were the dominant environmental factors that affected the distribution of DMS and DMSP in autumn. These results of this study would be of great significance in understanding the biochemical cycle of DMS in BS and NYS.

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Exploiting the gut microbiota to predict the origins and quality traits of cultured sea cucumbers - Zelong Zhao; Jingwei Jiang; Jie Zheng; Yongjia Pan; Ying Dong; Zhong Chen; Shan Gao; Yao Xiao; Pingzhe Jiang; Xuda Wang; Gaohua Zhang; Bai Wang; et al. (Environmental Microbiology, 2022)
Summary Nowadays, the true economic and nutritional value of food is underpinned by both origin and quality traits, more often expressed as increased quality benefits derived from the origin source. Gut microbiota contribute to food metabolism and host health, therefore, it may be suitable as a qualifying indicator of origin and quality of economic species. Here, we investigated relationships between the gut microbiota of the sea cucumber ( Apostichopus japonicus ), a valuable aquaculture species in Asia, with their origins and quality metrics. Based on data from 287 intestinal samples, we generated the first biogeographical patterns for A . japonicus gut microbiota from origins across China. Importantly, A . japonicus origins were predicted using the random forest model that was constructed using 20 key gut bacterial genera, with 97.6% accuracy. Furthermore, quality traits such as saponin, fat and taurine were also successfully predicted by random forest models based on gut microbiota, with approximately 80% consistency between predicted and true values. We showed that substantial variations existed in the gut microbiota and quality variables in A . japonicus across different origins, and we also demonstrated the great potential of gut microbiota to track A . japonicus origins and predict their quality traits.

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Knowledge Difference of Tumor Nutrition Risk Among Thoracic Cancer Patients, Their Family Members, Physicians, and Nurses - Jiaojiao Suo; Yu Sun; Weigang Xiu; Yan Fu; Yijia Qin; Lili Zhong; Jialong Han; Huijie Zhou; Hao Wei; Yan Wang; Jiang Zhu (Journal of Cancer Education, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Predisposition to atrioventricular septal defects may be caused by SOX7 variants that impair interaction with GATA4 - Baolei Li; Zhuoyan Li; Jianping Yang; Nanchao Hong; Lihui Jin; Yuejuan Xu; Qihua Fu; Kun Sun; Yu Yu; Yanan Lu; Sun Chen (Molecular Genetics and Genomics, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Neutrophil Extracellular Traps may be a Potential Target for Treating Early Brain Injury in Subarachnoid Hemorrhage - Hanhai Zeng; Xiongjie Fu; Jing Cai; Chenjun Sun; Mengyan Yu; Yucong Peng; Jianfeng Zhuang; Jingyin Chen; Huaijun Chen; Qian Yu; Chaoran Xu; Hang Zhou; et al. (Translational Stroke Research, 2022)

PL57 garnet as a new natural reference material for in situ U–Pb isotope analysis and its perspective for geological applications - Dengfeng Li; Yu Fu; Pete Hollings; Roger H. Mitchell; Shannon Zurevinski; Sandra Kamo; Rongqing Zhang; Yu Zhang; Qiaofen Liu; Jianlin Liao; Yongjia Liang; Xiaoming Sun (Contributions to Mineralogy and Petrology, 2022)

Exercise Ameliorates Fluoride-induced Anxiety- and Depression-like Behavior in Mice: Role of GABA - Qiqi Cao; Jixiang Wang; Yanru Hao; Fangye Zhao; Rong Fu; Yanghuan Yu; Jundong Wang; Ruiyan Niu; Shengtai Bian; Zilong Sun (Biological Trace Element Research, 2022)

Optimal array layout of cylindrical baffles to reduce energy of rock avalanche - Yu-zhang Bi; Dong-po Wang; Xian-lei Fu; Yi-xiong Lin; Xin-po Sun; Zhe-yuan Jiang (Journal of Mountain Science, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Physical Responses of Pinctada fucata to Salinity Stress - Jingru Yang; Jinling Yang; Mingqiang Chen; Zhengyi Fu; Jing Sun; Gang Yu; Aimin Wang; Zhenhua Ma; Zhifeng Gu (Frontiers in Marine Science, 2022)
This study was conducted to understand the changes of physiological and biochemical indexes of black and red shell Pinctada fucata under acute high and low salt stress. In this study, the salinity of 35‰ was used as the control, while the salinities of 20 and 50% salinity were used as the low and high salt treatment groups, respectively. The osmotic pressure (OSM) and ion concentration in the hemolymph, Na + -K + -ATPase (NKA) activity and respiratory metabolism in gills, and antioxidant and immune (non) enzymes in the hepatopancreas of P. fucata with two shell colors were compared and analyzed at the time periods of 1.5 and 3 h post-salinity stress. The results showed that the OSM and inorganic ion (Na + , Ca 2+ , and Cl – ) concentration in the hemolymph of the black and red P. fucata increased significantly with the increase of salinity after the time periods of 1.5 and 3 h. At 3 h, the black P. fucata NKA activity decreased significantly with the increase of salinity, while red P. fucata reached the highest value at high salinity. The succinate dehydrogenase (SDH) and lactate dehydrogenase (LDH) activities of red P. fucata showed U-shaped and inverted U-shaped distributions with the increase of salinity after 1.5 h, respectively. With the increase of salinity, the phenoloxidase (POX) activity of red and black P. fucata showed inverted U-shaped and U-shaped distributions, respectively. The contents of glutathione (GSH) and vitamin C (VC) in black P. fucata decreased significantly with the increase of salinity at 1.5 and 3 h. Red P. fucata GSH and VC reached their maximum value in the 1.5-h low salinity group and 3-h high salinity group. The vitamin E (VE) content in black P. fucata increased significantly with the increase of salinity at 1.5 h, and reached the maximum at 3 h in the control group. Red P. fucata VE reached the maximum at 1.5 and 3 h in the control group. The results obtained from the present study revealed that the sensitivity of P. fucata to salinity varied in shell color. Compared to black P. fucata , red P. fucata responds more quickly to sharp salinity changes, thereby reducing more likely damage. Compared with a high salt environment, P. fucata was more adaptable to the changes of acute low salt environment. The results obtained from the present study provide the physical references for subsequent selective breeding of this species.

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Genome sequence analysis of Cronobacter phage PF-CE2 and proposal of a new species in the genus Pseudotevenvirus - Mengshi Xiao; Xinmiao Ren; Ying Yu; Han Sun; Haijin Mou; Xiaodan Fu (Archives of Virology, 2021)

miR-106b-5p upregulation is associated with microglial activation and inflammation in the mouse hippocampus following status epilepticus - Tao Yu; Hui Fu; Jing-Jing Sun; Dan-Rui Ding; Hua Wang (Experimental Brain Research, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Pharmacological Activation of RXR-α Promotes Hematoma Absorption via a PPAR-γ-dependent Pathway After Intracerebral Hemorrhage - Chaoran Xu; Huaijun Chen; Shengjun Zhou; Chenjun Sun; Xiaolong Xia; Yucong Peng; Jianfeng Zhuang; Xiongjie Fu; Hanhai Zeng; Hang Zhou; Yang Cao; Qian Yu; et al. (Neuroscience Bulletin, 2021)

High resolution mapping of nighttime light and air pollutants during the COVID-19 lockdown in Wuhan - Sheng Zheng; Yuyuan Fu; Yu Sun; Chengjie Zhang; Yueshe Wang; Eric Lichtfouse (Environmental Chemistry Letters, 2021)

A Comparative Study on Low and High Salinity Tolerance of Two Strains of Pinctada fucata - Jing Sun; Mingqiang Chen; Zhengyi Fu; Jingru Yang; Shengjie Zhou; Gang Yu; Wenli Zhou; Zhenhua Ma (Frontiers in Marine Science, 2021)
This study compares salinity tolerance between red and black shell Pinctada fucata salinity stress of 20 and 50‰, while 35‰ was used as a control. The hemolymph osmotic pressure, inorganic ion concentration, the activities of Na + -K + -ATPase, respiratory metabolism related enzymes and liver tissue antioxidant related enzymes were measured at 12 and 24 h after salinity stress. The osmotic pressure and inorganic ion concentration of hemolymph of two strains P. fucata increased significantly with the increase of salinity. The activity of Na + -K + -ATPase of red P. fucata only decreased under low salinity at 24 h, and was significantly higher than that the control under low salinity at 12 h and high salinity at 12 and 24 h. The succinate dehydrogenase (SDH) activities of the P. fucata treatment groups were significantly higher than those the control at 12 h. The lactate dehydrogenase (LDH) activity increased significantly with salinity at 12 h. and the black P. fucata LDH activity was significantly higher than the control at 24 h, while the LDH activity of red P. fucata was significantly lower than that the control in 50‰ salinity. The superoxide dismutase (SOD) activity of black P. fucata was significantly lower than that the control, while that of red P. fucata was significantly higher than that the control within 24. At 12 h, the catalase (CAT) activity of red P. fucata increased significantly with salinity, but decreased significantly with salinity at 24 h. The CAT activity of black P. fucata was highest at 24 h under low salinity. Glutathione peroxidase (GSH-Px) and alkaline phosphatase (AKP) activities of red P. fucata were significantly higher than those the control under low or high salinity. At high salinity for 24 h, the GSH-Px activity was lowest in black P. fucata , AKP activity was highest. The present study indicates that the physical responses of P. fucata to the salinity stress vary with shell colors. The red P. fucata can quickly respond positively to the change of environmental salinity and reduce the damage caused by the change of environmental salinity.

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Houcaris gen. nov. from the early Cambrian (Stage 3) Chengjiang Lagerstätte expanded the palaeogeographical distribution of tamisiocaridids (Panarthropoda: Radiodonta) - Yu Wu; Dongjing Fu; Jiaxin Ma; Weiliang Lin; Ao Sun; Xingliang Zhang (PalZ, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Spatial prediction of soil calcium carbonate content based on Bayesian maximum entropy using environmental variables - Mei Shan; Shuang Liang; Hongchen Fu; Xiaoli Li; Yu Teng; Jingwen Zhao; Yaxin Liu; Chen Cui; Li Chen; Hai Yu; Shunbang Yu; Yanling Sun; et al. (Nutrient Cycling in Agroecosystems, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Spatiotemporal characteristics of sea ice transport in the Baffin Bay and its association with atmospheric variability - Weifu Sun; Haibo Bi; Min Fu; Xi Liang; Yunhe Wang; Yu Liang; Jue Huang; Haijun Huang; Liwen Yan; Qinglong Yu; Shuang Liang (Acta Oceanologica Sinica, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

The process of embryo abortion of stenospermocarpic grape and it develops into plantlet in vitro using embryo rescue - Shasha Li; Keke Liu; Saisai Yu; Shanshan Jia; Shuo Chen; Yuheng Fu; Feng Sun; Qiangwei Luo; Yuejin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Latitudinal differences in early growth of largehead hairtail ( Trichiurus japonicus ) in relation to environmental variables - Peng Sun; Qi Chen; Caihong Fu; Yi Xu; Runlong Sun; Jianchao Li; Haiqing Yu; Chi Zhang; Yang Liu; Zhenjiang Ye; Yongjun Tian; Mikko Heino (Fisheries Oceanography, 2020)
Largehead hairtail ( Trichiurus japonicus ) in the China Seas shows an increasing catch trend, despite continued overexploitation, which could be attributed to improved recruitment as a result of strengthened early growth. To understand the early growth variability of largehead hairtail, we examined the linkages between early growth, as revealed by otolith microstructure, and the associated environmental variables over both spatial and temporal scales. Young‐of‐the‐Year largehead hairtail were collected from three regions in the Bohai, Yellow and East China Seas between 29° and 39° N. Daily increment widths of sagittal otoliths were measured and used as a proxy for somatic growth. We found two spawning cohorts, Spring‐ and Summer‐spawned cohorts, that showed latitudinal differences in both mean growth and growth pattern. The transition time from larval to juvenile stage was identified at around 40 days. Daily increment widths of two cohorts showed similar growth pattern in the first 40 days, while location had a marked effect on daily growth over 41–110 days. This suggests physiologically constrained growth pattern in larval stage, but more plastic growth subject to habitat‐specific influences in juvenile stage. The gradient forest analysis identified sea bottom temperature, vertical temperature gradient, and sea surface salinity, as the most important variables in determining early growth. Latitudinal differences in early growth pattern and their response to environmental variables suggest adaptive plasticity of early growth, which has notable implication for the management and sustainable utilization of this important but heavily exploited resource in the China Seas.

Spatiotemporal variability of physical-biogeochemical processes and intrinsic correlations in the semi-enclosed South Yellow Sea - Qinsheng Wei; Baodong Wang; Mingzhu Fu; Junchuan Sun; Qingzhen Yao; Ming Xin; Zhigang Yu (Acta Oceanologica Sinica, 2020)

Climate Variability Patterns and Their Ecological Effects on Ecosystems in the Northwestern North Pacific - Shuyang Ma; Yongjun Tian; Jianchao Li; Haiqing Yu; Jiahua Cheng; Peng Sun; Caihong Fu; Yang Liu; Yoshiro Watanabe (Frontiers in Marine Science, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Science and Prediction of Heavy Rainfall over China: Research Progress since the Reform and Opening-Up of New China - Yali Luo; Jisong Sun; Ying Li; Rudi Xia; Yu Du; Shuai Yang; Yuanchun Zhang; Jing Chen; Kan Dai; Xueshun Shen; Haoming Chen; Feifan Zhou; et al. (Journal of Meteorological Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Progranulin alleviates podocyte injury via regulating CAMKK/AMPK-mediated autophagy under diabetic conditions - Di Zhou; Meng Zhou; Ziying Wang; Yi Fu; Meng Jia; Xiaojie Wang; Min Liu; Yan Zhang; Yu Sun; Yabin Zhou; Yi Lu; Wei Tang; et al. (Journal of Molecular Medicine, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Panax notoginsenoside Rb1 Restores the Neurotrophic Imbalance Following Photothrombotic Stroke in Rats - Chun-Yan Yang; Jian-Yu Yang; Yun-Xia Xiong; Xue-Feng Zhuang; Hui Su; Sheng Hu; Jia-Qing Ma; Xin-Fu Zhou; Hai-Yun Luo; Jun Sun (Neurotoxicity Research, 2019)

Gangliosides profiling in serum of breast cancer patient: GM3 as a potential diagnostic biomarker - Qinying Li; Mei Sun; Mingsheng Yu; Qianyun Fu; Hao Jiang; Guangli Yu; Guoyun Li (Glycoconjugate Journal, 2019)

Evaluating three satellite-based precipitation products of different spatial resolutions in Shanghai based on upscaling of rain gauge - Weiyue Li; Xiaogang He; Weiwei Sun; Marco Scaioni; Dongjing Yao; Jing Fu; Yu Chen; Bin Liu; Jun Gao; Xin Li; Guodong Cheng (International Journal of Remote Sensing, 2019)

The anther-specific CYP704B is potentially responsible for MSG26 male sterility in barley - Juan Qi; Fei Ni; Xiao Wang; Meng Sun; Yu Cui; Jiajie Wu; Allan Caplan; Daolin Fu (Theoretical and Applied Genetics, 2019)

A Highly Selective Fluorescence “Turn on” and Absorbance-Ratiometric Detection of Al3+ in Totally H2O and its Application in Test Paper - Xue-Jiao Sun; Yu-Qing Ma; Hong Fu; Zhi-Yong Xing; Zhi-Gang Sun; Yue Shen; Jin-Long Li (Journal of Fluorescence, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Physical-biogeochemical interactions and potential effects on phytoplankton and Ulva prolifera in the coastal waters off Qingdao (Yellow Sea, China) - Qinsheng Wei; Baodong Wang; Qingzhen Yao; Zhigang Yu; Mingzhu Fu; Junchuan Sun; Bochao Xu; Linping Xie; Ming Xin (Acta Oceanologica Sinica, 2019)

Isolation and identification of a vegetative organ-specific promoter from maize - HaoQiang Yu; Muhammad Hayder Bin Khalid; FengZhong Lu; FuAi Sun; JingTao Qu; BingLiang Liu; WanChen Li; FengLing Fu (Physiology and Molecular Biology of Plants, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Mapping of QTLs controlling seed weight and seed-shape traits in Brassica napus L. using a high-density SNP map - Lijie Sun; Xiaodong Wang; Kunjiang Yu; Wenjing Li; Qi Peng; Feng Chen; Wei Zhang; Sanxiong Fu; Dongqin Xiong; Pu Chu; Rongzhan Guan; Jiefu Zhang (Euphytica, 2018)

Shifts in the structure and function of the microbial community in response to metal pollution of fresh water sediments in Finland - Xue-Ping Chen; Hao-Yu Chen; Jing Sun; Xu Zhang; Chi-Quan He; Xiao-Yan Liu; Xin Huang; Min Yang; Fu-Shun Wang; Kristiina Väänänen (Journal of Soils and Sediments, 2018)

Total and available metal concentrations in soils from six long-term fertilization sites across China - Dong-Xing Guan; Fu-Sheng Sun; Guang-Hui Yu; Matthew L. Polizzotto; Yun-Gen Liu (Environmental Science and Pollution Research, 2018)

A novel Scan SAR imaging method for maritime surveillance via L p regularization - Jia-cheng Ni; Qun Zhang; Yu-fu Yin; Ying Luo; Li Sun (International Journal of Remote Sensing, 2018)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)

Quantification and comparison of acidic polysaccharides in edible fish intestines and livers using HPLC-MS/MS - Shuang Song; Qi Yu; Bao Zhang; Chunqing Ai; Yujiao Sun; Yinghuan Fu; Meiyu Zhao; Chengrong Wen (Glycoconjugate Journal, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Offshore detachment of the Changjiang River plume and its ecological impacts in summer - Qinsheng Wei; Zhigang Yu; Baodong Wang; Hui Wu; Junchuan Sun; Xuelei Zhang; Mingzhu Fu; Changshui Xia; Huiwu Wang (Journal of Oceanography, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Influences of Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on Heavy Metals and Inorganic Nitrogen Transformation in the Rice Field Surface Water - Qiaogang Yu; Junwei Ma; Wanchun Sun; Hui Lin; Qiang Wang; Jianrong Fu (Water, Air, & Soil Pollution, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

A Meta-analysis of the Effects of Experimental Warming on Plant Physiology and Growth on the Tibetan Plateau - Gang Fu; Zhen-Xi Shen; Wei Sun; Zhi-Ming Zhong; Xian-Zhou Zhang; Yu-Ting Zhou (Journal of Plant Growth Regulation, 2015)

Characterization and high expression of recombinant Ustilago maydis xylanase in Pichia pastoris - Hongjuan Han; Shuang You; Bo Zhu; Xiaoyan Fu; Baihui Sun; Jin Qiu; Chengye Yu; Lei Chen; Rihe Peng; Quanhong Yao (Biotechnology Letters, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Effect of different sulfides on cadmium distribution during sludge combustion based on experimental and thermodynamic calculation approaches - Jing-Yong Liu; Jie-Wen Fu; Shui-Yu Sun; Xun-An Ning; Yu-Jie Wang; Tao Chen; Guang-Qian Luo; Wu-Ming Xie; Zuo-Yi Yang; Zhong-Xu Zhuo (Environmental Science and Pollution Research, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Ectopic expression of Dendrobium EREB5 gene in Arabidopsis influences leaf morphology - Yuqiang Sun; Ying Shen; Anna Li; Wenfeng Fu; Yu Wang; Qicai Ying; Juan Hao; Brian Jones; Bo Shen; Huizhong Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Spatial structure of eukaryotic ultraplankton community in the northern South China Sea - Zhao-Yu Jiang; You-Shao Wang; Fu-Lin Sun (Biologia, 2014)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Microbial community shift with decabromodiphenyl ether (BDE 209) in sediments of the Pearl River estuary, China - Peng Wu; You-Shao Wang; Cui-Ci Sun; Fu-Lin Sun; Yu-Tu Wang (Biologia, 2013)

Identification of the proteins in green cotton fiber using a proteomics-based approach - Yan-Jun Li; Fu-Xin Wang; Ya-Qin Wang; Yong-Chang Liu; Xin-Yu Zhang; Yu-Qiang Sun; Jie Sun (Biotechnology Letters, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Knockdown of dishevelled-1 attenuates cyclosporine A-induced apoptosis in H9c2 cardiomyoblast cells - Yejing Zhu; Jinyu Chi; Yue Liu; Yihua Sun; Yu Fu; Xiaohui Zhang; Xueliang Ding; Xinhua Yin; Dechao Zhao (Molecular and Cellular Biochemistry, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

The contribution of intersubspecific hybridization to the breeding of super-high-yielding japonica rice in northeast China - Jian Sun; Di Liu; Jia-Yu Wang; Dian-Rong Ma; Liang Tang; Hong Gao; Zheng-Jin Xu; Wen-Fu Chen (Theoretical and Applied Genetics, 2012)

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Water quality criteria for 4-nonylphenol in protection of aquatic life - BingLi Lei; Qian Liu; YanFeng Sun; YiPei Wang; ZhiQiang Yu; XiangYing Zeng; JiaMo Fu; GuoYing Sheng (Science China Earth Sciences, 2012)

DJ-1 may contribute to metastasis of non-small cell lung cancer - Jing Bai; Changlong Guo; Wenjing Sun; Ming Li; Xiangning Meng; Yang Yu; Yan Jin; Dandan Tong; Jingshu Geng; Qi Huang; Jiping Qi; Songbin Fu (Molecular Biology Reports, 2012)

PKCα take part in CCR7/NF-κB autocrine signaling loop in CCR7-positive squamous cell carcinoma of head and neck - Zhao Zhen-jin; Li Peng; Liu Fa-yu; Sun Liyan; Sun Chang-fu (Molecular and Cellular Biochemistry, 2011)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

The polymorphisms of the TNF-α gene in multiple sclerosis?—a meta-analysis - Lidan Xu; Weiguang Yuan; Haiming Sun; Xuelong Zhang; Xueyuan Jia; Chao Shen; Yanling Zhao; Donglin Sun; Yang Yu; Yan Jin; Songbin Fu (Molecular Biology Reports, 2011)

PTOV1 is associated with UCH-L1 and in response to estrogen stimuli during the mouse oocyte development - Yu-Wei Yao; Yan Shi; Zhe-Fu Jia; Ya-Hong Jiang; Zheng Gu; Jian Wang; Mohamad Aljofan; Zhao-Gui Sun (Histochemistry and Cell Biology, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Major Ecosystems in China: Dynamics and Challenges for Sustainable Management - Yihe Lü; Bojie Fu; Wei Wei; Xiubo Yu; Ranhao Sun (Environmental Management, 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Lonicera confusa has an anatomical mechanism to respond to calcium-rich environment - Geng Wu; Maoteng Li; Fangxu Zhong; Chunhua Fu; Jing Sun; Longjiang Yu (Plant and Soil, 2011)

A haplotype in the CCR5 gene promoter was associated with the susceptibility to HIV-1 infection in a northern Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Xueyuan Jia; Chao Shen; Yanling Zhao; Yan Jin; Yang Yu; Hong Ling; et al. (Molecular Biology Reports, 2011)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Diversity of five novel Y-STR loci and their application in studies of north Chinese populations - Zhaoyang Xu; Haiming Sun; Yang Yu; Yan Jin; Xaingning Meng; Donglin Sun; Jing Bai; Feng Chen; Songbin Fu (Journal of Genetics, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

Expression of P2X6 receptors in the enteric nervous system of the rat gastrointestinal tract - Qiang Yu; Zhengqing Zhao; Jihu Sun; Wei Guo; Jiqiang Fu; Geoffrey Burnstock; Cheng He; Zhenghua Xiang (Histochemistry and Cell Biology, 2010)

CCR2-64I allele is associated with the progression of AIDS in a Han Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Yan Jin; Yang Yu; Feng Chen; Jing Bai; Hong Ling; Kaili Wang; et al. (Molecular Biology Reports, 2010)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

Biosynthesis of short-chain-length-polyhydroxyalkanoates during the dual-nutrient-limited zone by Ralstonia eutropha - Qun Yan; Ying Sun; Lifang Ruan; Jian Chen; Peter Hoi Fu Yu (World Journal of Microbiology and Biotechnology, 2005)

Impact of oil field exploitation on eco-environment of the Daqing lakes - Shao-peng Yu; Jin-fu Lu; Guang-you Sun (Chinese Geographical Science, 2003)

Relations of soil properties to topography and vegetation in a subtropical rain forest in southern Taiwan - Zueng-Sang Chen; Chang-Fu Hsieh; Feei-Yu Jiang; Tsung-Hsin Hsieh; I-Fang Sun (Plant Ecology, 1997)